NURSE'S ROLE IN CARING FOR A PATIENT WITH FOURNIER'S GANGRENE - Mitko Imirski; Diana Paskaleva (Peytchinski Publishing, 2024)
Fournier's gangrene is a life-threatening condition characterized by rapidly progressive necrotizing fasciitis, often leading to sepsis and multiple organ failure. While historically associated with males, the condition can affect both genders, with varying degrees of severity. This case report explores the complex management of a 59-year-old male patient with a history of alcohol abuse, diabetes, cirrhosis, and a long-term smoking habit, who presented with Fournier's gangrene. The patient's critical condition and complex medical history presented significant challenges for healthcare providers, particularly nurses, who played a pivotal role in his care. These cases occur rarely in practice and require specific care and compliance with surgical nursing techniques per protocol. This case report not only sheds light on the growing incidence of Fournier's gangrene among both genders but also underscores the indispensable role of nurses in the multidisciplinary care of patients with this challenging condition. Comprehensive nursing care, patient education, and meticulous attention to detail are essential in improving patient outcomes and reducing mortality rates associated with Fournier's gangrene.